HEAD HEARTS HANDS: Bringing together Christian thought, passion and action - DENNIS P. HOLLINGER (Droners Grove, Illinois InterVarsity Press, 2005)
In this book ethicist Dennis P. Hollinger presents a holistic, integrative vision for reuniting Christian thought, passion and action. He shows how individuals, churches and movements throughout history have focused on either the head, or the heart or the hands--often to the exclusion of other expressions. But by linking our intellect, emotions and actions, Hollinger points us toward a whole faith for the whole person, where each dimension feeds, nurtures and sustains the others.